Ceramics in the burial rites of the Neolithic-Early Bronze Age in the Ukrainian steppe - Nadezhda Kotova; Larissa Spitsyna (Documenta Praehistorica, 2010)
Numerous Neolithic/Bronze Age burials have provided important information about the appearance and development of the tradition of using pottery in burial rites among the Pontic steppe population. The first pottery has been dated to the first period of the Azov-Dnieper culture (5950– 5300 calBC). The small sherds found in graves were the remains of broken vessels used during funeral feasts on the surfaces of cemeteries. During the Early Eneolithic the sacrificial sites of the Azov-Dnieper culture became larger and included numerous broken pots, which were made especially for funeral feasts. Under the influence of the Balkans, the population of Sredniy Stog Eneolithic began to place vessels in graves, and continued to use pottery during funeral feasts near graves. The Middle and Late Eneolithic populations retained these traditions.